Granitóides proterozóicos como marcadores da evolução geotectônica da região nordeste do Pará, Brasil - PALHETA, Edney Smith de Moraes (2015)
Granitoids cropping out inside Phanerozoic sedimentary cover in northeast Pará, Brazil (Gurupi region), records the geotectonic evolution of this region. 207Pb/206Pb single zircon evaporation ages were obtained for different granitoid bodies of the region, besides Sm-Nd isotopic studies. Almost all the plutons are genetically related with regional geological processes operative during this crustal segment formation, which includes the São Luís Craton. Such processes are associated with amalgamation of island arcs and Archean nuclei during the Palaeoproterozoic (2.15 to 2,07 Ga). The reworking of the southwestern margin of the São Luís Craton at the end of the Neoproterozoic formed the Gurupi Belt and is recorded by the occurrence of a granitic pluton of 549 ± 4 Ma.